Dynamics of secondary forests in slash-and-burn farming: interactions among land use types in the Peruvian Amazon - Smith, J.; Kop, P. van de; Reategui, K.; Lombardi, I.; Sabogal, C.; Díaz, A. (1999)
The regeneration of secondary forests (SF) on previously cleared land in the Amazon is a promising development within the generally pessimistic scenario about tropical deforestation. This has stimulated efforts to augment the value of SF to farmers to induce them to increase the area in SF. The objective of this paper was to document the regeneration of SF in slash-and-burn agriculture and to develop policy and technological recommendatios for conserving forest cover on small farms and improve farmer welfare. The dynamics of SF in slash-and-burn farming were studied by investigating changes in the role of SF with frontier development. Farm survey data form a colonist settlement area in the Peruvian Amazon were analyzed by using a recursive econometric model. Results confirmed that substantial areas of SF exist on slash-and-burn farms during the first few deacdes after settlement. As a result, over third of the farm area is under forest cover. This implies that deforestation in slash-and-burn farming may be less than previously believed. Soil recuperation is the most important reason for the existence of SF in slash-and-burn agriculture. During the relatively early stages of frontier development studied in this paper, fallow periods increased over time as site productivity declined, giving rise to secondary forests. Pastures lowered forested areas on farms and appear to impede the regeneration of SF. Commercial exploitation of SF products was minimal and declines with frontier development. The conclusions show that improved short-rotation fallows may recuperate the soil at the expense of forest cover, particularly in areas where most of the forest cover consists of SF. This conflict could be resolved by technologies that enrich SF and reinforce its multiple functions, including soil recuperation. Reduction of extensive cattle ranching may be a more effective way to conserve forest cover in slash-and-burn farming than technologies for shortening fallow periods. A 'quantum leap' in the benefits of forested land will be required if increases in forest cover are to be compatible with farmer welafre. This is likely to require innovative approaches, such as commercialization of the environmental services of forests. The results of this research could be potentially shift efforts to control deforestation away from slash-and-burn farmers, thus reducing the perceived conflict between forest conservation and the livelihood of poor people.